Recent progress in natural seaweed pigments: Green extraction, health-promoting activities, techno-functional properties and role in intelligent food packaging - Muhammad Faisal Manzoor; Muhammad Talha Afraz; Betül Bay Yılmaz; Muhammad Adil; Naeem Arshad; Gulden Goksen; Murtaza Ali; Xin-An Zeng (Journal of Agriculture and Food Research, 2024)
Edible seaweed is a worthwhile source of natural pigments (NPs) such as carotenoids, chlorophylls, and phycobiliproteins, and these functional ingredients have been well-acknowledged due to their beneficial therapeutic properties. Green extraction techniques are the best option to generate them more effectively by shorter extraction times, lower operational temperatures, reduced solvent use, and process automation aid in efficient compound retrieval. These NPs show valuable biological properties such as neuroprotective, anti-cancer, antioxidant, anti-inflammatory, anti-bacterial, anti-angiogenic, and anti-obesity activities—the therapeutic potential of NPs highlights their potential applications in food industries. NPs are frequently used as food colorants, providing nutritional value and enhancing the sensorial and techno-functional properties of the final product. Also, the use of these NPs is presently being expanded to intelligent food packaging to observe food freshness and as a time-temperature indicator to improve the food properties and shelf life. Properly using seaweed in foods could incline a novel segment of seaweed-based hybrid/composite health foods. This review critically analyzes the recent advances from 2015 to 2023 in seaweed NPs' green extraction, their therapeutic properties, potential techno-functional properties ensuing in food items, and their role in intelligent food packaging systems.